Analyzing Emotional Styles in the Field of Christian Religion and the Relevance of New Types of Visualization - Herbrik, Regine (Qualitative Sociology Review, 2012)
In the following text the theoretical conception, the employed analysis methods and some first results of the research project “The Emotionalization of Religion” are presented. The aim of the project is to compare newer Christian congregations with a Pentecostal or evangelical orientation to Christian parishes affiliated with the Evangelical Church in Germany or the Roman Catholic Church with regard to their respective emotional culture. The employed method set includes several qualitative methods, such as videoanalysis, the analysis of guideline interviews and participant observation. A particular focus lies within the empirical paragraph on the question: What role do new types of media usage in Christian parishes play for the development, representation and analysis of new emotional styles?